EFFECT OF INCUBATION PERIOD AT 30°C AND AT 40°C ON POSTTHAW CHARACTERISTICS OF FROZEN SEMEN OF HF CROSSBRED BULLS - SHRIVATAVA, NOOPUR; AWASTHl, M K; SAHU, S B; SAHASTRABUDHE, S; TIWARI, R P (The Indian Journal of Animal Reproduction, 2023)
To observe the effect of post-thaw incubation periods, frozen semen samples of six HF crossbred bulls werethawed at 37°C for 30 seconds and thawed semen was evaluated immediately at O min and after 15, 30, 45 and 60min of incubation at 30°C and 4°C, respectively. There was non-significant difference in post-thaw motility between30°C and 4°C at each incubation period except at 15 min of incubation. Non-significant difference was recorded inpost-thaw viability during incubation at 15, 30, 45 and 60 min between 30°C and 4°C temperature. Higher proportion(P< 0.05) of HOST positive spermatozoa were recorded at 30, 45 and 60 min of incubation at 4°C than at 30°C.There was non-significant difference in proportion of spermatozoa with intact acrosome between 30°C and 4°C atall incubation periods. Post-thaw motility was recorded nearly 50 per cent at 15 min of incubation with bothincubation temperatures and therefore, it may be suggested that frozen-thawed semen may be used for inseminationup to 15 min by keeping frozen-thawed semen straw either at 4°C or in warm water at 30°C after thawing at 37°Cfor 30 seconds.
Keywords: Crossbred bulls; frozen semen; post-thaw semen characteristics